THE CASHLESS REVOLUTION : CHINA'S REINVENTION OF MONEY AND THE END OF AMERICA'S DOMINATION OF FINANCE AND TECHNOLOGY - Chorzempa, Martin (New York, NY : PublicAffairs, 2022)
"The future of finance - the way Wall Street operates and how individuals manage their money - is on the verge of upheaval. And the force underlying the change comes from China, where finance and technology are being merged into a system with consequences that resonate far beyond China's border. The changes of this global revolution in finance and technology - fintech - will be as powerful as those wrought in social media, retailing and advertising by giants such as Amazon, Facebook, Google, and Twitter, which have overturned how we shop and communicate"-- Provided by publisher
In English, with some text in Chinese
Keywords: Finance -- China; Finance -- Technological innovations -- China; Digital currency -- China; Money -- China; China -- Economic conditions; Informational works